2021
DOI: 10.3390/en14217325
|View full text |Cite
|
Sign up to set email alerts
|

Banks’ Energy Behavior: Impacts of the Disparity in the Quality and Quantity of the Disclosures

Abstract: Environmental, social, and governance (ESG) factors are becoming increasingly relevant for banks as entities that play an essential role in supporting the development of enterprises, individuals and the whole economy. The paper aims to evaluate the impact of the ESC directive on banks’ energy behavior disclosures, explicitly relating to behaviors towards energy use and its impact on banks’ performance. We developed a methodology to provide the objective characteristic of banks’ energy behavior. In the paper, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Other studies showed that there is evidence about a move towards the environmental practices and sales volume, which proves that the environmental disclosure and its reports contribute significantly to improving the reputation and image of companies conducting these practices (Mattera et al, 2021;Mohammad & Wasiuzzaman, 2021;Lubis & Rokhim, 2021). The results of other studies also indicated that there is a relation between the environmental activities and the profitability of companies carrying out them in many countries (Buallay, 2021;Klimontowicz et al, 2021).…”
Section: First: Strategy Of the Environmental Performancementioning
confidence: 93%
See 1 more Smart Citation
“…Other studies showed that there is evidence about a move towards the environmental practices and sales volume, which proves that the environmental disclosure and its reports contribute significantly to improving the reputation and image of companies conducting these practices (Mattera et al, 2021;Mohammad & Wasiuzzaman, 2021;Lubis & Rokhim, 2021). The results of other studies also indicated that there is a relation between the environmental activities and the profitability of companies carrying out them in many countries (Buallay, 2021;Klimontowicz et al, 2021).…”
Section: First: Strategy Of the Environmental Performancementioning
confidence: 93%
“…Among the reasons that result in the reputational risks are the existence of some cases and lawsuits or some internal violations such as internal fraud and misrepresentation in the financial data (Gillan et al, 2021). Moreover, the existence of some harmful environmental practices for society leads to undermining the confidence of stakeholders in the company (Buallay, 2021;Klimontowicz et al, 2021). Among what causes the reputational risks also are that have arised from the weak governance mechanisms in companies (Gennaro & Nietlispach, 2021).…”
Section: Second: the Reputational Risksmentioning
confidence: 99%
“…Considering that active transmission causes losses which are usually considered to be a small constant value, the marginal price of active power is consistent at all nodes; the general form of the marginal price at node i is shown in (12):…”
Section: Economic Value Of Reactive Power Demandmentioning
confidence: 99%
“…where α clear is the marginal market-clearing price; ∂P loss ∂P i is the net loss sensitivity of nodal active injection; and ∂P loss ∂Q i is the net loss sensitivity of nodal reactive power injection. (12) shows that the value of reactive power demand is attached to the price of electricity commodities in the electricity market through the incremental cost caused by net loss. It can be seen that the smaller the reactive power demand of an electricity commodity, i.e., the higher the power factor, the lower the price of the electricity commodity; at the same time, the smaller the fluctuation in power factor, the smaller the fluctuation in the price of the electricity commodity.…”
Section: Economic Value Of Reactive Power Demandmentioning
confidence: 99%
See 1 more Smart Citation